Design and development of a durable series elastic actuator with an optimized spring topology. (December 2021) - Yildirim, Mehmet C; Sendur, Polat; Kansizoglu, Ahmet Talha; Uras, Umut; Bilgin, Onur; Emre, Sinan; Yapici, Guney Guven; Arik, Mehmet; Ugurlu, Barkan
This paper aims to present the integrated design, development, and testing procedures for a state-of-the-art torsion-based series elastic actuator that could be reliably employed for long-term use in force-controlled robot applications. The main objective in designing the actuator was to meet weight and dimensional requirements whilst improving the long-term durability, ensuring high torque output, and containing its total weight. A four-fold design approach was implemented: (i) following recursive design-and-test procedures, an optimal torsional spring topology was unveiled with the help of SIMP (Solid Isotropic Material with Penalization) topology optimization method, (ii) the proposed spring was manufactured and multiple specimens were experimentally tested via a torsional test machine to validate linearity, loading rate response, and mechanical limits, (iii) the actuator's thermal response was experimentally scrutinized to ensure that the generated heat was dissipated for long-term use, and (iv) the fatigue life of the spring was computed with the help of real-life experiment data. Having concluded the development and verification procedures, two different versions of the actuator were built, and preliminary torque control experiments were conducted. In conclusion, favorable torque tracking with a bandwidth of 19 Hz was achieved while peak-to-peak torque input was 20 Nm.